Analisis de modelos de produccion para Populus x euramericana en la Cuenca del Duero - Bravo, E.=700 1 Grau, J.M.; Gonzalez Antoñanzas, F.
(En, Es)
ilus., 33 ref.
Keywords: MODELOS; PRODUCCION; CRECIMIENTO; POPULUS; ESPAÑA; ALAMO